Conquests in eleventh-century England 1016, 1066 - Ashe, Laura ca. 20./21. Jh; Ward, Emily Joan ca. 20./21. Jh (The Boydell Press, 2020)
The cataclysmic conquests of the eleventh century are here set together for the first time
Title from publisher's bibliographic system (viewed on 30 Apr 2020)
Keywords: Knut -- Dänemark, König -- 995-1035; Geschichte 1001-1100; Geschichte 1015-1020; Geschichte 1001-1016; Geschichte 1066-1070; Assandun, Battle of, England, 1016; Hastings, Battle of, England, 1066; Königin; Wirtschaft; Recht; Politische Elite; Interkulturalität; Wandel; Kunst; Dänen; Kooperation; Eroberung; Normannische Eroberung Englands; Genealogie; Konfrontation; Kirchenreform; Kultur; Mäzen; Frau; Great Britain -- History -- Canute, 1017-1035; Great Britain -- History -- William I, 1066-1087; Skandinavien; Nordseeraum; Europa; England